Lavandula angustifolia and Lavandula latifolia Essential Oils from Spain: Aromatic Profile and Bioactivities - Carrasco, Alejandro; Martinez-Gutierrez, Ramiro; Tomas, Virginia; Tudela, Jose (Planta Medica, 2016)
Compositions of true lavender (Lavandula angustifolia) and spike lavender (Lavandula latifolia) essential oils, cultivated and extracted in the Southeast of Spain, were determined by gas chromatography coupled with mass spectrometry detection, obtaining both relative (peak area) and absolute (using standard curves) concentrations. Linalool (37–54 %), linalyl acetate (21–36 %) and (E)-β-caryophyllene (1–3 %) were the most abundant components for L. angustifolia. Linalool (35–51 %), eucalyptol (26–32 %), camphor (10–18 %), α-pinene (1–2 %), α-terpineol (1–2 %) and α-bisabolene (1–2 %) were the most abundant components for L. latifolia. The characterization was completed with enantioselective gas chromatography, in which the determined main molecules were (−)-linalool, (−)-linalyl acetate and (+)-camphor. (S)-(−)-camphene, (R)-(+)-limonene, (1R, 9S)-(−)-(E)-β-caryophyllene and (1R, 4R, 6R, 10S)-(−)-caryophyllene oxide were found in this study as the predominant enantiomers in Spanish L. angustifolia. The characterised essential oils were tested for their antioxidant activity against free radicals ABTS, DPPH, ORAC, chelating, and reducing power. Inhibitory activity on lipoxygenase was observed indicating a possible anti-inflammatory activity, mainly due to linalool, camphor, p-cymene and limonene. These results can be the starting point for a future study of the potential use of L. angustifolia and L. latifolia essential oils as natural cosmetic and natural pharmaceutical ingredients for several skin diseases.
Keywords: Lavandula angustifolia; Lavandula latifolia; Lamiaceae; essential oil; enantiomeric ratio; antioxidant; LOX inhibitory activity